ANALISIS GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN DISIPLIN KERJA DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR CAMAT KOTA JUANG KABUPATEN BIREUEN - Marlina Marlina; Mohd. Tasar (IndOmera, 2025)
This study aims to analyze the transformational leadership style and work discipline in improving employee performance at the Kota Juang Sub-district Office. This study uses inductive methods and descriptive analysis with qualitative techniques. The results of this study showed that so far the leaders at the Kota Juang Sub-district Office, Bireuen Regency were also less able to provide full direction and guidance to employees, regarding optimal guidance or direction for employees achieved by participating in training held by the company. The leaders of the Kota Juang Sub-district Office, Bireuen Regency have so far paid less attention to their employees in discipline when coming to work or leaving early because they considered that the attendance system was the main controller so that leaders did not care too much about it. The performance of the employees at the Kota Juang Sub-district Office, Bireuen Regency has not been in accordance with the procedures established by the institution. Keywords: transformational leadership style, work discipline and employee performance